A suspension of inactivated bacteria used for vaccination against recurrent urinary tract infections increases the phagocytic activity of murine macrophages - Eggers, Anja; Ballüer, Melissa; Mohamed, Belal A.; Nau, Roland; Seele, Jana (Frontiers in Immunology, 2023)
Background. Urinary tract infections are a major cause of the consumption of antibiotics in humans.We studied the effect of a vaccine (StroVac®, containing inactivated bacteria and used to prevent recurrent urinary tract infections) licensed in Germany on the release of pro-inflammatory cytokines and the phagocytosis of Escherichia (E.) coli in primary murine macrophages and the macrophage cell line J774A.1.StroVac® increased the release of the cytokines TNF-α, IL-6, IL-12/23 p40 and IL-1β and stimulated the phagocytosis of E. coli in a dose-dependent manner. This effect was independent of LPS as shown by the usage of macrophages isolated from LPS-resistant C3H/HeJ mice. At concentrations up to 30 mg/l it was not toxic to bacteria or eukaryotic cells.StroVac® does not only act via the adaptive, but also by stimulating the innate immune system. This stimulation may help to build trained innate immunity against bacterial pathogens involved in recurrent urinary tract infections.